2021
DOI: 10.21203/rs.3.rs-154102/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Operationalization of COVID-19 Rapid Diagnosis Using Xpert® Xpress SARS CoV-2 Assay in Resource-Limited Settings: Early Implementation Lessons From Uganda

Abstract: Introduction: The novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that causes COVID-19 disease is a global challenge. Several countries have adopted testing, isolation, and tracing strategy towards the control of the COVID-19 pandemic, but access to rapid and accurate testing is still a global challenge. The conventional PCR – based assay is the most commonly used test yet it has huge costs, infrastructural, and procurement logistical challenges. The Xpert® Xpress SARS-CoV-2 test is an auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The implementation of diagnostic procedures in the context of the COVID-19 pandemic has been fraught with numerous challenges and barriers, particularly in resource-limited settings. The global challenge of access to rapid and accurate testing has been exacerbated by infrastructural and logistical challenges, including supply chain shortages and the availability of testing centers (Nsawotebba et al, 2021). The Democratic Republic of Congo (DRC), for instance, has faced several exacerbating factors contributing to a poor healthcare system, including conflict, healthcare resource constraint and exhaustion, poor infrastructure, insufficient logistical resources, limited testing centers, and a lack of personal protective equipment (PPE).…”
Section: Overcoming Challenges and Barriers In Diagnostic Implementationmentioning
confidence: 99%
See 1 more Smart Citation

Review of Laboratory Diagnostics Evolution in Nigeria's Response to Covid-19

Chinedu Paschal Maduka,
Adebukola Adejumoke Adegoke,
Chiamaka Chinaemelum Okongwu
et al. 2023
imsrj
“…The implementation of diagnostic procedures in the context of the COVID-19 pandemic has been fraught with numerous challenges and barriers, particularly in resource-limited settings. The global challenge of access to rapid and accurate testing has been exacerbated by infrastructural and logistical challenges, including supply chain shortages and the availability of testing centers (Nsawotebba et al, 2021). The Democratic Republic of Congo (DRC), for instance, has faced several exacerbating factors contributing to a poor healthcare system, including conflict, healthcare resource constraint and exhaustion, poor infrastructure, insufficient logistical resources, limited testing centers, and a lack of personal protective equipment (PPE).…”
Section: Overcoming Challenges and Barriers In Diagnostic Implementationmentioning
confidence: 99%
“…In Uganda, the operationalization of Xpert® Xpress SARS-CoV-2 testing faced several challenges, including infrastructural modifications and the establishment of robust Laboratory Quality and Information Management Systems. Despite these challenges, the implementation team successfully established the Xpert® Xpress SARS-CoV-2 testing Laboratory, which significantly reduced the median turnaround time for samples compared to before it was established (Nsawotebba et al, 2021). The integration of innovative solutions such as machine learning methods with routinely available laboratory results can be useful when the relationship between individual analytes and disease state is complex or unknown.…”
Section: Addressing Logistical and Infrastructural Constraints And Li...mentioning
confidence: 99%

Review of Laboratory Diagnostics Evolution in Nigeria's Response to Covid-19

Chinedu Paschal Maduka,
Adebukola Adejumoke Adegoke,
Chiamaka Chinaemelum Okongwu
et al. 2023
imsrj
“…A second 42-day lockdown was also instituted in April of 2021 with comparable, albeit less restrictive policies. During the initial lockdown period and initial phases of the pandemic TB testing platforms were repurposed to test for COVID-19 and TB clinic staff were affected by transportation restrictions and were reassigned to COVID-19 units leading to reports of understaffing [14,15]. Clinics also employed strategies to ensure continuation of essential TB services which included: financial incentives for healthcare workers, PPE distribution and dispensing medications for multiple months during refills [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that since up to 70% of patients, who were diagnosed with SARS-CoV-2 by RT-PCR, showed no or minimal symptoms, they pose a significant risk for spreading infection (Xu et al 2021). However, none of the currently used methods are reliable and/or applicable for mass screening of this infection in public places ( Martinez-Jimenez et al, 2021 , Nsawotebba et al, 2021 , Sharun et al 2020, Peeling et al 2021 ). The reverse transcription polymerase chain reaction (RT-PCR) test is a routine diagnostic tool to detect patients infected with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%